Students' Perception of Using Group Work in English Class - Situmorang, Monica Amelia (JET (Journal of English Teaching), 2021)
Group work has become an essential part of modern methodology in teaching and learning because it offers teachers a powerful way to engage students and provides students with opportunities for cooperative learning. This study aimed to find out the students’ perception of using group work in English classes. Employing a survey design involving 50 tenth and eleventh graders, it was conducted in SMA 17 Agustus 1945 Jakarta. Data were collected through a questionnaire including five indicators. The collected data were analyzed using the descriptive technique. Findings revealed that group work had a positive impact on students’ attitudes. Moreover, group work enlarged their commitment in completing assignments.